EVALUATION OF MATURITY LEVEL AND DESIGN OF INCIDENT MANAGEMENT SOP IN ACADEMIC INFORMATION SYSTEM USING ITIL V4 - Febrian, Dany; Salisah, Febi Nur; Megawati, Megawati; M.Afdal; Marsal, Arif (Informatika, Universitas Jenderal Soedirman, 2024)
STIKES is one of the universities that organizes study programs that focus on Health Professional Education, one of which is STIKES XYZ Pekanbaru. STIKES XYZ should be able to utilize technology to support the performance and processes carried out in the educational environment. The Academic Information System (SIADAK) is a system at STIKES XYZ which is used by all lecturers and students. This system can be accessed online, however, the process that occurs when the system is used does not necessarily run well, there are still several things that must be considered, starting from maintenance and management of problems that occur. Therefore, maturity level measurements are carried out as well as designing standard operational procedures for incident management. This research uses the Information Technology Infrastructure Library Framework 4 and uses incident management practice as a guide for measuring maturity levels and designing SOPs for handling problems. Based on the results of data collection and processing based on practice incident management, it was found that the maturity level was at level 2 (Repeatable) and the SOP for handling problems was designed. Based on the results of the maturity level and the design of SOPs for handling problems with the academic information system, they can be used as a reference to further improve the quality of services and the quality of the Academic Information System.